2021
DOI: 10.1038/s41389-021-00357-4
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the CIC-DUX4 oncogene through P300/CBP inhibition, a therapeutic approach for CIC-DUX4 sarcoma

Abstract: CIC-DUX4 sarcoma (CDS) is a highly aggressive and metastatic small round type of predominantly pediatric sarcoma driven by a fusion oncoprotein comprising the transcriptional repressor Capicua (CIC) fused to the C-terminal transcriptional activation domain of DUX4. CDS rapidly develops resistance to chemotherapy, thus novel specific therapies are greatly needed. We demonstrate that CIC-DUX4 requires P300/CBP to induce histone H3 acetylation, activate its targets, and drive oncogenesis. We describe the syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…The DUX4 C‐terminus recruits p300/CBP, inducing a drastic increase of histone H3K27 acetylation, and p300 inhibition induces cell death via global histone H3 hyperacetylation 109,110 . The finding was supported by the result that the treatment with the p300/CBP inhibitor iP300w inhibited the proliferation of CIC::DUX4 sarcoma cells 111 . CIC::DUX4 upregulates genes of oncogenic pathways such as ETV1/4/5 and Cyclin D/E 112,113 .…”
Section: Epigenetic Aberrations In Bone and Soft Tissue Sarcomas And ...mentioning
confidence: 92%
“…The DUX4 C‐terminus recruits p300/CBP, inducing a drastic increase of histone H3K27 acetylation, and p300 inhibition induces cell death via global histone H3 hyperacetylation 109,110 . The finding was supported by the result that the treatment with the p300/CBP inhibitor iP300w inhibited the proliferation of CIC::DUX4 sarcoma cells 111 . CIC::DUX4 upregulates genes of oncogenic pathways such as ETV1/4/5 and Cyclin D/E 112,113 .…”
Section: Epigenetic Aberrations In Bone and Soft Tissue Sarcomas And ...mentioning
confidence: 92%
“…1k). The DUX4 activation domain is exquisitely dependent on the histone acetyltransferase (HAT) activity of p300 and CBP 27,28 . We found that H3 acetylation driven by sDUX was reversed by treatment with iP300w (Fig.…”
Section: Sdux Binds Dux Motifs and Is Toxic To Human Myoblastsmentioning
confidence: 99%
“…NCC-CDS2-C1 cells harbored a CIC::DUX4 fusion without insertion and exhibited rapid growth, spheroid formation, and invasion. Bosnakovski et al [28 ▪ ] have demonstrated that the CIC::DUX4 chimeric protein requires P300/CBP to induce histone H3 acetylation, activate its targets, and drive oncogenesis. They have described the synthetic route to a selective and highly potent P300/CBP inhibitor named iP300w and related stereoisomers, and found that iP300w efficiently suppress CIC::DUX4 transcriptional activity and reverses CIC::DUX4 induced histone H3 acetylation.…”
Section: Therapeutic Options For Cic-dux4 Sarcomamentioning
confidence: 99%